Sosialisasi Protokol Kesehatan bagi Anak-anak dan Pencegahan Covid-19 di Desa Banyuwangi Kabupaten Serang - Ibrohim Ibrohim; Ulfi Jefri; Rina Agustina; Silvi Sri Mulyaningsih (Gapenas Publisher, 2022)
COVID-19 is a virus that attacks the respiratory system, adversely affecting health accompanied by mild and severe symptoms. Severe symptoms caused. this virus is transmitted through physical contact, wearing items alternately with patients who are positive for COVID-19, not wearing a mask when talking to COVID-19 sufferers, and so on. This virus is a disease that is not predicted to occur in advance. The signs and symptoms of COVID-19 are classified as severe, the occurrence of acute respiratory syndrome, causing pneumonia and the most fatal resulting in death, while the mild symptoms are fever, sneezing, sore throat. Banyuwangi Village is a village located in Puloampel District, Banyuwangi area is included in the Serang Regency of Banten Province. During the current COVID-19 pandemic, of course, the community hopes that students can play an active role in breaking the chain of spread of COVID-19. The approach method that we apply in community service is to use the socialization method about the importance of implementing health protocols